A categoria da ação política em Hannah Arendt - Martins, Jeferson Tadeu (2018)
This work aims to study the category of political action in the book The Human Condition by Hannah Arendt. This is a category that evidences the search of the author in valorizing the vita activa, understood as labor, work and action. Considering that the totalitarianism of the twentieth century caused a rupture with the tradition of western political thought, Arendt proposes to think of the category of political action from a recovery of what she believes has been relegated to oblivion throughout tradition, to investigate some political phenomena, as originally manifested. In this dissertation, after the proposal of Arendt’s work is presented in general, the author's understanding about vita activa was evidenced, briefly addressing the categories of labor and work, and then presenting the main aspects of the action, based on the book The Human Condition. Finally, Arendt's analysis of modernity is clarified, along with the process of alienation from the world and the reflection on the system of councils, in which, for Arendt, political action is manifested in an authentic way